The Influence of RADEC-Based Learning Model Tools on Enhancing Students’ Innovation Creativity in Nature-Based Elementary Schools - Yusuf, Furtasan Ali; Fajari, Laksmi Evasufi Widi (FKIP Universitas Lampung, 2025)
Abstract: The Influence of RADEC-Based Learning Tools on Enhancing Students’ Innovation Creativity in Nature-Based Elementary Schools. Objectives: The lack of innovative and effective learning tools presents a challenge in enhancing students' creativity, necessitating an examination of the influence of RADEC-based learning tools as an alternative solution in natural elementary schools. This study aims to examine the influence of RADEC-based learning tools on enhancing students' innovation creativity in natural elementary schools. Methods: The research method employed is a quantitative method with a quasi-experimental model, utilizing the One Group Pretest-Posttest Design and the Pretest-Posttest Control Group Design. The sample consists of the innovation creativity of 50 students from two natural elementary schools, with 25 students in each school. The testing technique uses open-ended test instruments based on indicators of innovation creativity. Data analysis involves descriptive statistical analysis, N-Gain, and t-tests. Findings: The research findings indicate: (1) the data on the creative innovation of the experimental class are in the medium category with a percentage of 80%, while the control class is at 48%; (2) the average N-Gain score for the control class is 0.17, categorized as low, while the experimental class achieves a score of 0.52, categorized as medium; and (3) the t-test shows a significance value (2-tailed) of 0.000 < 0.05 and a t-value of 5.636 > 1.677, indicating a difference in the influence of implementing RADEC-based learning tools and conventional learning tools on improving the innovation creativity of students in natural elementary schools. Conclusion: The conclusion of this study is that RADEC-based learning tools are effective in improving the innovation creativity of students in natural elementary schools, with better results compared to conventional learning tools. Keywords: learning tools, RADEC model, innovation creativity, elementary school students, natural schools.